1999
DOI: 10.1093/jac/44.5.629
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of omeprazole, amoxycillin plus metronidazole versus omeprazole, clarithromycin plus metronidazole on the oral, gastric and intestinal microflora in Helicobacter pylori-infected patients

Abstract: Fourteen patients with Helicobacter pylori infection were treated with 20 mg omeprazole, 1 g amoxycillin and 400 mg metronidazole bd for 7 days (OAM), and 16 patients were treated with 20 mg omeprazole, 250 mg clarithromycin and 400 mg metronidazole bd for 7 days (OCM). Saliva, gastric biopsies and faecal samples were collected before, during (day 7) and 4 weeks after treatment in order to analyse alterations of the normal microflora and to determine antimicrobial susceptibility. Both treatment regimens result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 21 publications
9
109
0
4
Order By: Relevance
“…Most of the bacteria identi®ed are normal inhabitants of the respiratory tract and oral cavity and, therefore, it might not be surprising if swallowed bacteria are found in the stomach. Moreover, these results are in good agreement with a recent study revealing the presence and distribution of a gastric mucosal micro¯ora in dyspeptic patients with H. pylori infection [24].…”
Section: Cloning and Dna Sequence Analysissupporting
confidence: 92%
“…Most of the bacteria identi®ed are normal inhabitants of the respiratory tract and oral cavity and, therefore, it might not be surprising if swallowed bacteria are found in the stomach. Moreover, these results are in good agreement with a recent study revealing the presence and distribution of a gastric mucosal micro¯ora in dyspeptic patients with H. pylori infection [24].…”
Section: Cloning and Dna Sequence Analysissupporting
confidence: 92%
“…The actinobacteria were particularly negatively impacted in both the throat and gut samples immediately after antibiotic treatment, presumably due to clarithromycin that is known to target this group. Adamsson et al (1999) also previously found that this antibiotic treatment regimen led to quantitative and qualitative alterations in the faecal microbiota and suggested that amoxicillin might be better from an ecological perspective than clarithromycin for eradication of H. pylori because it resulted in less emergence of resistant strains.…”
Section: Impact Of Antibiotics On Normal Gut Microbiota Compositionmentioning
confidence: 88%
“…However, little is known about other members of the human gastric microbial ecosystem in disease and health. Characterization of the gastric microbiota has traditionally relied on cultivation of gastric juice or mucosal biopsies, and such studies have identified several members of the Firmicutes, Proteobacteria, Actinobacteria, and Fusobacteria phyla, as well as yeasts in relatively low abundance (2,3). The relative paucity of cultivated bacteria and the presence of a harsh local environment have led to assumptions that the human stomach does not harbor a complex microbial biota.…”
mentioning
confidence: 99%